'Refugee Protest Camp Vienna': making citizens through locations of the protest movement. Issue 5 (3rd July 2016) - Ataç, Ilker
Abstract: The Refugee Protest Camp Vienna started in 2012 as a protest against the living conditions found within the biggest reception centre in Austria, and turned into a highly visible protest movement organized by asylum seekers and activists. In this paper, I investigate how and to what extent this protest movement, through a form of contentious politics, succeeded in challenging exclusionary policies and improving asylum seekers' rights and living conditions. By moving from socially and spatially isolated locations into the centre of the city, setting up a protest camp in a park, and by seeking shelter in a church, the protest movement generated different modes of resistance, forms of mobilization and collective action. In exploring the connection between spatial strategies of the protest movement and relational ties within the movement, I contribute to debates within Critical Citizenship Studies. Specifically, I emphasize the relevance of place for creating alliances and networks and for making citizens.